KONTRIBUSI PENDAPATAN PEKERJA USAHA TAHU NIPON TERHADAP PENDAPATAN KELUARGA DI DESA TATELI KECAMATAN MANDOLANG KABUPATEN MINAHASA - Bima Satria Mohamad Noor; Elsje Pauline Manginsela; Welson Marthen Wangke (AGRI-SOSIOEKONOMI, 2019)
The purpose of this study was to determine the income contribution of Tahu Nipon Business workers to family income and the time allocation on Tahu Nipon Business workers. This research was conducted for three months, starting from January to March 2019. The data used in this study were primary data and secondary data. Primary data was obtained from direct interviews with workers and business owners of Tahu Nipon Business. Secondary data is obtained from the Office of The North Sulawesi Central Statistics Agency and Tateli Village Office; and the internet through google books and google scholarships to get journal articles and thesis related to the topic of this research, namely the contribution of workers 'income to family income and the outpouring of workers' time. The sampling method is a census with the number of respondents 6 workers. The results of this study indicated that the average income contribution of Tahu Nipon Business workers is 83.33% of family income. The average time spent by Tahu Nipon Workers in the research area in one day for domestic activities is 2.08 hours per day with a percentage of 8.66%, while the time spent on productive activities is 8.33 hours per day with a percentage of 34.70 %, and time for other activities besides taking care of family and work, including sleep rest, averaging 13.5 hours per day with a percentage of 56.25%.*eprm*